Kajian Potensi Ekowisata Di Lereng Selatan Taman Nasional Gunung Merapi Untuk Pengembangan Paket Wisata Minat Khusus - , Pitaya ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Southern slope of Mount Merapi National Park is the touristic area fulfill with the beautifull nature panorama, biodiversity and social culture potentials. Nowadays, such various potentials not yet intensifically developed, so some crucial conservation problems still occur in that area. Thus ecotourism development in the form of special interest tour package could be the answer to force the environmental care-based tourism activity. The aims of the research are 1) To study the nature resources and culture potentials in the southern slope area of Mount Merapi National Park, 2) To know the native community wants according to the tourism activitvity in southern slope of Mount Merapi National Park, 3) To analize the tourist interest about the various tourism attraction, their hopes and activities they want to do in the southern slope area of Mount Merapi National park. Method used in this research was descriptive analysis to the nature resources and social culture potentials inventory founded in the southern slope area of Mount Merapi National Park, supported by SWOT analysis. Data was collected through literature studies, direct field observation, questionnaires filled by 134 respondents, and also in depth interview with the 15 community leaders, tourism service businessman, area authority and government services. The result of the analysis shows that ecotourism potentials in the southern slope of Mount Merapi National Park can be developed in the form of special interest tour package, which all stakeholders in that area could be contribute in it. Wishes in the future, not only local community economic empowerment could be done but also helping the physical and non physical environment conservation in that area.